Fragmenty dwóch nieznanych druków z oficyny Jana Hallera (z 1506 i 1509 roku) - Łukaszewski, Jakub (Biblioteka Uniwersytecka w Poznaniu, 2016)
W komunikacie opisano odnalezione w Archiwum Archidiecezjalnym w Gnieźnie fragmenty dwóch nieznanych druków z oficyny Jana Hallera. Są to pozostałości dwóch egzemplarzy Ars Minor Aeliusa Donata (wydane 24 grudnia 1506) oraz drukowany formularz mandatu arcybiskupa Andrzeja Boryszewskiego (wydany ok. 12 marca 1509–przed 8 kwietnia 1509).

The communique describes the fragments of two unknown prints from the printing office of Jan Haller that have been found in the Archdiocese Archives in Gniezno. These are the remnants of two copies of the Ars Minor by Aelius Donat (published Dec. 24, 1506) and a printed form of the mandate for Archbishop Andrzej Boryszewski (issued approximately on March 12, 1509, but before Apr. 08, 1509).
Fragments of two unknown prints from Jan Haller printing office (from 1506 and 1509)
Keywords: Jan Haller; Donatus; Ars Minor; Andrzej Boryszewski; starodruki; old prints; typografia; typography; Archiwum Archidiecezjalne w Gnieźnie; Archdiocese Archives in Gniezno